PWE-097 Classification of pseudomyxoma peritonei as low or high grade according to the WHO criteria is prognostically significant. (28th May 2012) - Carr, N; Moran, B; Cecil, T; Chandrakumaran, K; Ilesley, I C; Mirnezami, A; Mohamed, F
Abstract : Introduction: The current WHO classification of tumours of the digestive system divides pseudomyxoma peritonei into two grades, namely low-grade and high-grade. This study was designed to correlate survival with low-grade and high-grade pseudomyxoma peritonei classified according to the WHO criteria. Methods: The histological slides of 274 consecutive patients were reviewed and designated as either low-grade or high-grade. The patients had been referred for cytoreductive surgery. The grade of the pseudomyxoma was correlated with survival data using the Kaplan–Meier method with the log-rank (Mantel-Cox) test. Results: 238 (87%) patients had low-grade lesions and 36 (13%) had high-grade lesions. The most common primary tumour was a low grade appendiceal mucinous neoplasm (231 cases, 84%). Seven patients who died within 30 days of their operation (a postoperative mortality of 2.6%) were excluded from survival analysis. Another patient was excluded because of incomplete survival data. The remaining 266 patients showed an overall 5-year survival of 63% in patients with low-grade pseudomyxoma peritonei and 23% in patients with high-grade pseudomyxoma peritonei (p<0.001). Complete cytoreduction was achieved in 165 (60%) patients; the 5-year survival for low-grade and high-grade was 84% and 48% respectively in this group (p<0.001). The median survival of patients who had complete cytoreduction was 7.7 years for low-grade and 2.8 years for high-grade (p<0.001). Conclusion: Histological classification of pseudomyxoma peritonei as low-grade or high-grade correlates with prognosis. This may identify a group who could benefit from further adjuvant therapy which is not generally advocated for appendiceal mucinous tumours. Competing interests: None declared.